Pengaruh Efisiensi Operasional dan Green Port Practices terhadap Kinerja Terminal Peti Kemas melalui Daya Saing Pelabuhan - Agus Leonard Togatorop; Awel Suryadi; Tri Budi Prasetya (Politeknik bumi Akpelni, 2026)
Container terminals play a strategic role in supporting maritime logistics and regional trade competitiveness. Increasing operational pressure and environmental concerns require terminal operators to improve efficiency while adopting green port practices. This study aims to analyze the effect of operational efficiency and green port practices on container terminal performance with port competitiveness as a mediating variable. A quantitative approach was employed using survey data collected from 90 respondents working in container terminal operations and management. Data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results indicate that operational efficiency and green port practices have a positive and significant effect on port competitiveness. Port competitiveness has a strong influence on container terminal performance. Operational efficiency directly affects performance, while green port practices do not show a significant direct effect. However, both variables significantly influence terminal performance through port competitiveness. These findings highlight the importance of integrating efficiency improvement and environmental initiatives into a comprehensive competitiveness strategy.